Handbook of nanostructured thin films and coatings - Zhang, Sam. (Boca Raton : CRC Press, 2010)
The first volume, Nanostructured Thin Films and Coatings: Mechanical Properties, covers the mechanical properties (i.e., hardness, toughness, and adhesion), including processing, properties, and performance. It also offers a detailed analysis of theories and size effect, in addition to other key topics. Volume Two, Nanostructured Thin Films and Coatings: Functional Properties, focuses on functional properties (i.e., optical, electronic, and electrical) and related devices and applications. The third volume, Organic Nanostructured Thin Film Devices and Coatings for Clean Energy, addresses various aspects of the processing and properties of organic thin films, devices, and coatings for clean energy applications. A complete resource, this handbook provides the detailed explanations for newcomers and the latest research and data for experts. Covering a wide range of mechanical and functional technologies, including those used in clean energy, these books feature figures, tables, and images that aid researchers and help professionals acquire and maintain a solid grasp of this burgeoning field.
[v. 1.] Nanostructured thin films and coatings : mechanical properties -- [v. 2.] Nanostructured thin films and coatings : functional properties -- [v. 3.] Organic nanostructured thin film devices and coatings for clean energy.
Includes bibliographical references and indexes.
1
Keywords: Thin films; Coatings; Nanostructured materials; Solar cells; Green technology; Computer storage devices